Shear strength behavior of cemented soil in direct simple shear - Kanesh Kanaraj Thangaraju. (2010)
Tropical soils such as residual soil are cemented to a certain degree. The shear strength behaviour of these soils may not be properly described by classical soil mechanics theories. The objective of this project is to study the effect of cementation and bonding on the shear strength properties of these soils by conducting direct simple shear tests in the laboratory. Artificially made soil samples will be tested. Samples with and without cementation will be tested and the results are compared and analysed.